UW Sinus Surgery Cadaver/Live Dataset (UW-Sinus-Surgery-C/L) - Lin, Shan; Qin, Fangbo; Bly, Randall A.; Moe, Kris S.; Hannaford, Blake (My University, 2020)
This dataset was developed at the University of Washington's BioRobotics Lab (http://brl.ee.washington.edu). It has endoscopic sinus surgery images with manual annotations for surgical instrument segmentation task. The challenging conditions of this dataset include specular reflections, blur from motion, blood, smoke and tools in shadow.
Keywords: Endoscopic sinus surgery; Instrument Segmentation